The perceived effects of urban renewal initiatives, such as NDPG-funded capital projects, as reported by Mdantsane's businesses on their operations. - Mseleni, Sizwe (My University, 2017)
As a result of apartheid planning, South Africa is left with a legacy of exclusionary planning, with many of its township areas still lacking necessary infrastructure, which has led to these areas lagging in development. Townships are one of the areas where this has been most evident and the post-apartheid government has the task of ensuring that their development is prioritised through public funding and public-private partnerships. The national government of South Africa has initiated a strategy to fund public infrastructure upgrades by funding local municipalities through the Neighbourhood Development Partnership Grant. The Buffalo City Metropolitan Municipality as a recipient of this grant, has initiated projects in the Mdantsane Township to initiate infrastructure-led development and subsequently improve the lives of the township’s inhabitants. Considering that the Mdantsane Central Business District (CBD) has been in existence for many decades, this study seeks to learn what impact the Urban Renewal Programme (URP) has had on the business sector and Local Economic Development (LED). The aim of the NDPG is to counter the effects of exclusionary planning and alleviate poverty by making the area more conducive for businesses operators and attractive to private investors. The aim of this research report is to gain insight into the perceptions of business owners and operators of the upgraded township CBD. The challenges of BCMM officials are also detailed in the research in order to gain insight into the issues hindering the state from offering efficient service delivery and development. The qualitative research method is applied and interviews are utilised as a research tools. Municipal officials also give their input into the challenges faced by their respective offices when planning and implementing URP projects. Insight is gained into the complex relations that affect the planning and implementation of successful infrastructure led economic development. BCMM officials involved in Urban Renewal need to prioritise service delivery, providing support to SMEs, crime prevention, improving design of planned projects in addition to infrastructure provision.
A research report submitted to the Faculty of Engineering and the Build Environment, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Masters of Science in Development Planning, 2017
Keywords: Urban renewal--South Africa; City planning--South Africa.